2018
DOI: 10.11114/jets.v6i2.2812
|View full text |Cite
|
Sign up to set email alerts
|

A Cross-Cultural Investigation of Gender-Bound Language Use in Turkish and English Plays: Implications for Foreign Language Education

Abstract: The aim of the study is to investigate gender-bound language use in Turkish and English languages and to identify the differences and similarities across cultures and genders in the plays with family and social themes. Four English and five Turkish plays were chosen randomly for comparison. The number of words in the plays were taken into consideration for an accurate and balanced analysis. For this reason, the closeness of the number of words used by male and female characters in the plays were more important… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Second, Genc and Armagan (2018) Different from the first and second studies, the third study was conducted by Zhiber & Korotina (2019) entitled "Intensifying adverbs in the English language" focusing on the use of intensifiers in daily spoken language and intensifiers in newspapers. It was concluded that newspapers rarely used intensifiers since the language was mainly formal.…”
Section: Attitudinal Disjunctsmentioning
confidence: 99%
“…Second, Genc and Armagan (2018) Different from the first and second studies, the third study was conducted by Zhiber & Korotina (2019) entitled "Intensifying adverbs in the English language" focusing on the use of intensifiers in daily spoken language and intensifiers in newspapers. It was concluded that newspapers rarely used intensifiers since the language was mainly formal.…”
Section: Attitudinal Disjunctsmentioning
confidence: 99%
“…Meanwhile, example 6 showed that she used the words "weighs heavily" in her utterance to express the great scale of "something" that she felt overburden herself at that time. Genc and Armagan (2018) found that intensifiers are adverbs that can be used to intensify the meaning of other words. In Mulan (2020) movie, the researchers found that Mulan used some adjectives that are categorized as this feature to strengthen her statements and showed her great feelings on something in some particular situations.…”
Section: 'Empty' Adjectivesmentioning
confidence: 99%